Mass selection for small‐sized cysts in Artemia franciscana produced in Vinh Chau salt ponds, Vietnam. Issue 10 (27th December 2012) - Van, Nguyen Thi Hong; Van Hoa, Nguyen; Bossier, Peter; Sorgeloos, Patrick; Van Stappen, Gilbert
Abstract Unidirectional mass truncation selection for small‐sized cysts was carried out on brine shrimp (Artemia franciscana Kellogg 1906), Vinh Chau strain, Vietnam, through cyst sieving and then culturing the selected individuals (<5% of the population) under field and laboratory conditions over two successive generations (F1 and F2). The results showed that at both culture scales, the cyst size of the selected line was smaller (P < 0.05) compared with the control (non‐selected) line, illustrating that there was a response to selection. The cyst size decreased about 3% per generation and the accumulated gain on the target trait was in the range 5.82–6.07% at the end of the selection process compared with the base population. The realized heritability estimation (h2) for cyst size was 0.23 ± 0.06 and 0.74 ± 0.19 in the field trials and 0.34 and 0.51 in the laboratory test for the F1 and F2 generation respectively. The variations found between the respective trials may be explained as the result of environmental interaction with the selection process, but the results show that a selection program for small‐sized cysts in Artemia by mass selection is possible.